2017
DOI: 10.12659/msm.902906
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box Protein J1 (FOXJ1) is Overexpressed in Colorectal Cancer and Promotes Nuclear Translocation of β-Catenin in SW620 Cells

Abstract: BackgroundFOXJ1, which is a forkhead transcription factor, has been previously studied mostly as a ciliary transcription factor. The role of FOXJ1 in cancer progression is still elusive and controversial. In the present study, the effect of FOXJ1 in progression of colorectal cancer (CRC) was investigated.Material/MethodsThe pattern of FOXJ1 expression was investigated using the method of immunohistochemistry (IHC) in a tissue microarray (TMA) incorporating 50 pairs of colon cancer specimens and adjacent normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The expression level of uroplakin-1b (UPK1B) is upregulated in bladder cancer, and it shows an oncogene function [ 33 ]. Forkhead box protein J1 (FOXJ1) is upregulated in bladder cancer and colorectal cancer [ 34 , 35 ] but downregulated in ependymoma and choroid plexus tumors [ 36 ]. The downregulated genes that we have identified in NPC, such as MSMB, UPK1B, and FOXJ1, may be associated with the development or progression of NPC and may play different roles from their roles in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of uroplakin-1b (UPK1B) is upregulated in bladder cancer, and it shows an oncogene function [ 33 ]. Forkhead box protein J1 (FOXJ1) is upregulated in bladder cancer and colorectal cancer [ 34 , 35 ] but downregulated in ependymoma and choroid plexus tumors [ 36 ]. The downregulated genes that we have identified in NPC, such as MSMB, UPK1B, and FOXJ1, may be associated with the development or progression of NPC and may play different roles from their roles in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 19 Wnt/β-catenin signaling pathway is a highly conserved molecular mechanism which was reported to play a crucial role in a variety of human malignancies, including ovarian cancer, hepatocellular carcinoma, breast cancer, and colorectal cancer, by activating its downstream targets including Cyclin D1, c-Myc, GSK-3, and so on. 20 23 To explore the association between CASC2 and Wnt/β-catenin signaling pathway, we measured the mRNA level of β-catenin, Cyclin D1, and c-Myc in glioma tissues and found that their levels increased significantly when compared to adjacent NBT. The discovery indicated a reciprocal relation between CASC2 and Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…FOXQ1 overexpression has been seen to play a relevant role in enhancing CRC tumorigenicity, tumour growth and migration/invasion of tumour cells by mainly acting on WNT and TGF-B molecular pathways [144, 190192]. Other FOX proteins having oncogenic properties in CRC would include FOXA1, FOXD1, FOXD3, FOXF1, FOXF2 FOXJ1, FOXK1, FOXK2, FOXN3 and FOXR2 [46, 47, 65, 193204]. Additional FOX TF studies have reported tumour suppressor properties for some of them, such as FOXE1, FOXF1, FOXF2 and FOXJ3 [205–210].…”
Section: Main Textmentioning
confidence: 99%